WACANA DAN CITRA POLITIK KANDIDAT PRESIDEN 2024 DI MEDIA SOSIAL - Aminulloh, Akhirul; Fianto, Latif (Jurnal Ilmu Sosial dan Ilmu Politik (JISIP), 2023)
The 2024 presidential election is still one year away. However, the clamor about who the presidential candidate or candidate is is already busy on social media. Social media has become a venue for discourse battles between presidential candidates in influencing public opinion. This study aims to analyze the political discourse and image of the 2024 presidential candidates on social media. This research uses the critical discourse analysis method from Faiclough. This method is used to reveal the ideology and power relations behind a discourse on social media. This research was conducted on the social media Twitter with a focus on the issue of Indonesia's cancellation as host of the U20 World Cup by FIFA and its impact on the political image of the 2024 presidential candidates. Data was taken with the help of NodeXL software to describe conversations about the issue that is the focus of this research. Data collection was carried out using documentation techniques in the form of tweets on the Twitter platform during the period 21-28 March 2023 and literature study. The results of this research show that the issue of the Israeli National Team's arrival in Indonesia for the U20 World Cup has become a battle for political discourse on social media influencing public opinion. This discourse became very political when it gave rise to debate which ended in support and rejection of the arrival of the Israeli National Team. This happens because support or rejection of this issue can be linked to the popularity and electability of political figures who will run as presidential candidates in the political contestation approaching 2024. However, the discourse of rejection of the arrival of the Israeli National Team has influenced the electability of the three presidential candidatesPemilihan presiden tahun 2024 masih satu tahun lagi. Namun, riuh gemuruh siapa calon atau kandidat presidennya sudah ramai di media sosial. Media social menjadi ajang pertarungan wacana antar kandidat presiden dalam mempengaruhi opini public. Studi ini bertujuan untuk menganalisis wacana dan citra politik kandidat presiden 2024 di media sosial. Penelitian ini menggunakan metode critical discourse analysis dari Faiclough. Metode ini digunakan untuk mengungkap ideologi dan relasi kuasa dibalik sebuah wacana di media social. Penelitian ini dilakukan pada media social Twitter dengan fokus pada isu pembatalan Indonesia sebagai tuan rumah piala dunia U20 oleh FIFA dan pengaruhnya terhadap citra politik kandidat presiden 2024. Data diambil dengan bantuan software NodeXL untuk menggambarkan percakapan tentang isu yang menjadi focus dalam penelitian ini. Pengumpulan data dilakukan dengan teknik dokumentasi berupa twit di platform Twitter selama periode 21-28 Maret 2023 dan studi pustaka. Hasil penelitian ini menunjukkan bahwa isu kedatangan Timnas Israel di Indonesia dalam rangka Piala Dunia U20 telah menjadi pertarungan wacana politik di media sosial memengaruhi opini publik. Wacana ini menjadi sangat politik ketika menimbulkan perdebatan yang berujung pada dukungan dan penolakan terhadap kedatangan Timnas Israel. Hal ini terjadi karena dukungan maupun penolakan isu ini bisa dikaitkan dengan popularitas dan elektabilitas tokoh politik yang akan maju menjadi calon presiden dalam kontestasi politik menjelang 2024. Walau bagaimana pun, wacana penolakan terhadap kedatangan Timnas Israel telah memengaruhi elektabilitas ketiga calon presiden tersebut